2022
DOI: 10.3390/cancers14153738
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes in Anal Canal Adenocarcinomas—A Systematic Review

Abstract: (1) Background: Anal canal adenocarcinomas constitute 1% of all gastrointestinal tract cancers. There is a current lack of consensus and NICE guidelines in the United Kingdom regarding the management of this disease. The overall objective was to perform a systematic review on the multitude of practice and subsequent outcomes in this group. (2) Methods: The MEDLINE, EMBASE, EMCARE and CINAHL databases were interrogated between 2011 to 2021. PRISMA guidelines were used to select relevant studies. The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, only 57% of patients receiving CRT subsequently had surgery. [6] Also Taliadoros [5] confirm that trimodality treatment with neoadjuvant chemoradiotherapy followed by radical surgery of abdominoperineal excision of rectum appeared to be the most effective approach.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, only 57% of patients receiving CRT subsequently had surgery. [6] Also Taliadoros [5] confirm that trimodality treatment with neoadjuvant chemoradiotherapy followed by radical surgery of abdominoperineal excision of rectum appeared to be the most effective approach.…”
Section: Discussionmentioning
confidence: 98%
“…Larger retrospective studies Franklin et al and Lewis et al [2,3] and a recent systematic of review of Talidaros [5] provided a more accurate analysis of the management and clinical outcomes of this tumor, showing as adenocarcinoma of the anus reported a more aggressive behavior in comparison to that of the squamous cell type and a worse prognosis than rectal adenocarcinoma. Although the National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines in Oncology, suggest for the management of anal adenocarcinoma neoadjuvant therapy followed by radical surgery with abdominoperineal resection (APR), [6] in clinical practice there is a lack of consensus regarding the optimal management, with some physicians advocating for trimodality therapy (similar to the paradigm employed in locally advanced rectal adenocarcinoma) [7] and others advocating for definitive radiation therapy with concurrent chemotherapy, with abdominoperineal resection (APR) employed for salvage of locally recurrent disease (similar to the management of anal squamous cell carcinoma).…”
Section: Introductionmentioning
confidence: 99%
“…The study included patients treated with chemotherapy alone, chemoradiotherapy with the inguinal area included in the irradiation field and chemoradiotherapy followed by chemotherapy before surgery, but whether there were any prognostic differences between these groups of patients is unknown [22]. While systematic reviews have found that preoperative chemoradiotherapy plus radical surgery for the primary lesion has the best prognosis [23,24], radiotherapy to the groin may not be necessary if ILND is performed because the effect of radiotherapy is local tumour control and the inguinal region is at the body surface, is easy to approach and does not have complicated anatomy. Another reason to omit radiotherapy is that lymphadenectomy plus adjuvant radiotherapy increases lower limb volume due to lymphoedema compared with lymphadenectomy alone [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, infrequently occurring instances concurrent to human papilloma virus (HPV) infection appear immune reactive to p16. 1,2 Additionally, adenocarcinoma of anal canal possibly emerges due to association with chronic anal fistula, anal Crohn's disease or anal sexual intercourse. 2,3 Adenocarcinoma of anal canal may represent within a fistula tract or appear as a vaginal cyst.…”
mentioning
confidence: 99%